KINSHIP LEVEL BETWEEN JAVANESE AND SUNDANESE LANGUAGES IN MEDAN NORTH SUMATERA - Indah Asriani Siregar; Amrin . Saragih; Siti Aisyah Ginting (LINGUISTIK TERAPAN, 2022)
ABSTRACT The aims of this study to determine the level of kinship. This study used a mixed method, employing 300 Swadesh vocabulary lists that have been modified to fit the Austronesian languages. The source of the data in this study is the informants who are the native speaker of Javanese and Sundanese language who live in Medan Tembung and Medan Timur, to pronounce the Javanese and Sundanese 300 Swadesh Vocabulary list.The Lexicostatistics approach was used to analyze the data. The result of data analysis revealed that there were 137 word pairs or 46% out of 300 swadesh vocabulary list. The kinship level of Javanese and Sundanese Languages is in of Family group.keywords must be written to describe the research scope observed, as well as the main terms undergirding the research